Geology, geochemistry and occurrence of rare earth elements in coal from the Soutbansberg West Coalfield (Mopane Sector). Limpopo Province, South Africa - Ntake, Mahlatse Manthepeng (My University, 2024)
The supply security of rare earth elements (REE) is a global key concern due to their scarcity and increasing demand. Consequently, the quest for alternative sources of REE is pivotal for countries that are reliant on REE imports, including South Africa. This search for new alternative non-conventional sources of these critical elements has sparked a heightened interest in coal deposits as the new alternative source. The Soutpansberg Coalfield of South Africa hosts substantial coal deposits. However, there is a gap in understanding the geology and geochemistry of the coals as well as the rare earth-bearing potential of this coalfield. Therefore, this study aims to investigate the geology, geochemistry and occurrence of rare earth elements in the coal stockpiles within the Mopane Sector of the Soutpansberg Coalfield. To fulfil the purpose of this study, coal petrography, proximate analysis, ultimate analysis, x-ray diffraction, scanning electron microscopy-energy dispersive spectrometry and inductively coupled plasma-mass spectrometry were used. Most of the coal stockpiles were ranked as high-volatile bituminous B-A coals distinguished by their high vitrinite, moderate to low liptinite and low inertinite macerals. Geochemically, the coals contained low moisture content with high ash yields and moderate volatile matter. Additionally, the coals contained low sulphur with high oxygen and carbon contents, corroborating their coke properties. The mineralogical analysis of the coals confirmed that the coals were predominantly composed of organic carbon (24% to 73%), quartz, kaolinite, plagioclase, siderite and other minerals. These coal stockpiles were further confirmed to contain the renowned rare-earth bearing minerals, including xenotime and monazite, associated with clay, quartz and other minerals. Several REE were detected within the samples, including Er, Tm, Ho, Gd, Yb, Lu, Sm, Eu, Tb, Pr, Dy, Nd, Ce, La, Sc, and Y, with the predominant REE being Ce. The total REE within each stockpile varied between 230 ppm and 670 ppm, with the stockpiles being enriched in light REE (2166.67 ppm) and depleted in heavy REE. Furthermore, the coal stockpiles exhibited high yields of excessive REE compared to the critical and uncritical REE. The stockpiles are of a sedimentary source with felsic and terrigenous associations. Ce and Eu anomalies suggest that the enrichment of the coals is of a detritic origin, which might be from the Limpopo Mobile Belt and the Beit Bridge Complex. The normalized REE concentrations of the samples were compared with those of Chinese, USA, UCC and MKB coals and they were found to be higher than all the aforementioned deposits. In addition, the coals fall within the promising regions for the economic extraction of the REE.
Thesis (M. Sc. (Geology)) -- University of Limpopo, 2025
Keywords: Rare earth elements; Soutpansberg Coalfield; Geology; Geochemistry; Occurrence; Concentration; Soil chemistry; Rare earths; Coal